Wicked plants : the weed that killed Lincoln's mother & other botanical atrocities - Stewart, Amy.; Morrow-Cribbs, Briony; Rosen, Jonathon (Chapel Hill, N.C. : Algonquin Books of Chapel Hill, 2009)
Stewart takes on more than 200 of Mother Nature's most appalling creations and offers this A-to-Z compendium of plants that kill, maim, intoxicate, and otherwise offend.
Aconite -- Arrow poisons -- Ayahuasca vine and chacruna -- Betel nut -- Castor bean -- Ordeal poisons -- Coca -- Coyotillo -- Deadly nightshade -- Death camas -- Deadly dinner -- Ergot -- Fatal fungus -- Habanero chili -- Henbane -- The Devil's bartender -- Iboga -- Jimson weed -- Botanical crime families -- Khat -- Killer algae -- Ragweed -- Kudzu -- Lawn of death -- Mala mujer -- Here comes the sun -- Manchineel tree -- Don't look now -- Mandrake -- Marijuana -- Oleander -- Forbidden garden -- Opium poppy -- Dreadful bouquet -- Peacock flower -- Peyote cactus -- Psychedelic plants -- Poison hemlock -- Purple loosestrife -- Weeds of mass destruction -- Ratbane -- Rosary pea -- The terrible toxicodendrons -- Sago palm -- More than one way to skin a cat -- Stinging tree -- Meet the nettles -- Strychnine tree -- Suicide tree -- Carnivores -- Tobacco -- Toxic blue-green algae -- Duck and cover -- Water hemlock -- Water hyacinth -- Social misfits -- Whistling thorn acacia -- White snakeroot -- Yew -- Poison gardens.
Includes bibliographical references (p. 233-[236])
Keywords: Poisonous plants; Dangerous plants; Plants, Toxic -- classification -- Popular Works